APA YANG HARUS KITA LAKUKAN PADA KASUS BULLYING ? IMPLIKASINYA TERHADAP MANAJEMEN BIMBINGAN DAN KONSELING DI SEKOLAH - Anaway I. Mansyur; Herdi Herdi (PSIKOLOGI KONSELING, 2020)
Teenagers who are victims of bullying are more at risk of experiencing various health problems, both physically and mentally. The problems that are more likely to be suffered by children who are victims of bullying, among others, the emergence of various mental problems such as depression, anxiety and sleep problems that may be carried into adulthood, physical health complaints, such as headaches, abdominal pain and muscle tension, a sense of not safe while in the school environment, and decreased learning enthusiasm and academic achievement. In fairly rare cases, children who are victims of bullying may show violence. Coloroso (2007) states that victims of bullying are usually new children in an environment, the youngest child in school, usually a smaller child, fearful, perhaps unprotected, a child who has experienced trauma or has been hurt before and is usually very sensitive, avoiding peers to avoid more severe pain, and find it difficult to ask for help. This article aims to find out about counseling service management in nine countries in overcoming the problem of bullying, and the factors that cause bullying. The data source of this paper is done by the documentation study method. In this article the results show that the factors that influence the occurrence of bullying can come from individuals, families, play groups, to the community environment of the perpetrators. This action is closely related to the world of social work, which in this case is required to be a counselor for bullying perpetrators.Keywords: Bullying; Counseling Service Management